Hemoglobin level associates with survival in women from Appalachian Kentucky with uterine cervix cancer - Kunos, Charles A.; Fabian, Denise; Fredericks, Tricia; Baldwin, Lauren; Dietrich, Charles; Miller, Rachel W.; Ueland, Frederick R. (Frontiers in Oncology, 2023)
The purpose of this retrospective study was to determine the relationship between pretherapy hemoglobin levels and progression-free survival among women with uterine cervix cancer undergoing concurrent weekly cisplatin and radiotherapy followed by brachytherapy. Patients with advanced-stage II-IVA uterine cervix cancer were grouped by hemoglobin level (Hgb > 12.0, 11.9-10.0, or < 10.0 g/dL). Endpoints were progression-free survival, overall survival, and local control. Between 01/2001 and 07/2022, 168 patients contributed demographic, tumor, pretherapy hemoglobin, and outcome data with a median follow-up of 31 months. Progression-free survival at three years was 73% (95% confidence interval: 58%-84%), 71% (95% confidence interval: 56%-82%), and 62% (95% confidence interval: 44%-75%) for the Hgb > 12.0, 11.9-10.0, or < 10.0 g/dL groups, respectfully (P < 0.001). In addition, pretherapy hemoglobin levels were significant with treatment outcome when included in a multivariate analysis of prognostic variables. In conclusion, the difference in pretherapy hemoglobin level was prognostic of progression-free survival.